2017
DOI: 10.1002/anie.201703225
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Dehydrogenase Reduces Cyanate to Cyanide

Abstract: The biocatalytic function of carbon monoxide dehydrogenase (CODH) has a high environmental relevance owing to its ability to reduce CO . Despite numerous studies on CODH over the past decades, its catalytic mechanism is not yet fully understood. In the present combined spectroscopic and theoretical study, we report first evidences for a cyanate (NCO ) to cyanide (CN ) reduction at the C-cluster. The adduct remains bound to the catalytic center to form the so-called CN -inhibited state. Notably, this conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…In addition to the Ni-C, a Fe-C bond stabilises the binding of CO, now in a bridging configuration, to the C-cluster. CO is isoelectronic to CN -, which represents an inhibitor of the reverse oxidation reaction catalysed by CODH 51,52 .…”
Section: Exploring the Free Energy Landscapesmentioning
confidence: 99%
“…In addition to the Ni-C, a Fe-C bond stabilises the binding of CO, now in a bridging configuration, to the C-cluster. CO is isoelectronic to CN -, which represents an inhibitor of the reverse oxidation reaction catalysed by CODH 51,52 .…”
Section: Exploring the Free Energy Landscapesmentioning
confidence: 99%
“…8,9 The W-L cycle, also known as the anaerobic acetyl-coenzyme A pathway, is found in anaerobic bacteria and archaea. 10 It is the oldest type of biofabricated carbon fixation, in which carbon monoxide dehydrogenase (CODH) efficiently catalyzes the reversible conversion of CO 2 to CO. 11 Numerous studies have been reported on the crystal structure and active reaction site of CODH, [12][13][14] which facilitated the artificial simulation of its active site for carbon capture. The CODH from Carboxydothermus hydrogenoformans contains homodimeric Ni-CODHs, with CODH I providing electrondriven proton translocation across the cytoplasmic membrane via the complex I-associated hydrogenase.…”
Section: Introductionmentioning
confidence: 99%
“…13 Despite exhibiting a very effective internal electron transfer mechanism and a suitable reaction environment, the CODH is quickly inactivated outside of living organisms because of its extreme sensitivity to oxygen and temperature. 11 To improve the stability and reproducibility of CODH, it has been immobilized on support materials like TiO 2 . 15–17 However, the activity of the enzyme is affected, or it even loses its biological function throughout the process of immobilization.…”
Section: Introductionmentioning
confidence: 99%